Crescimento, partição de assimilados e acúmulo de macronutrientes pelo tomateiro `SM-16` em diferentes coberturas do solo - Lucena, Rafaella Rayane Macedo de (Universidade Federal Rural do Semi-Árido, 2011)
The determination of growth rates and accumulation of nutrients is important because they provide information on the nutritional requirement of plants, indicating the times are more conducive to application of nutrients. The use of soil cover has become a widespread practice and has led to an increase in growth and productivity in various vegetables, including the tomato plant. Aiming to evaluate the growth, assimilate partitioning and accumulation of nutrients by tomato 'SM-16'in different soil covers led to an experiment in WG Fruits, Baraúna / RN, between September 2009 and January 2010. The experimental design adopted was a randomized complete block with four replications. Treatments were arranged in split plots with the plots represented by the types of soil cover: bare soil, black polyethylene film, white polyethylene film, polyethylene film and polypropylene gray black (TNT), and sub-plots by the time of samplings of the plants: 14, 28, 42, 56, 70, 84, 98 and 112 days after transplanting (DAT). The characteristics evaluated were: accumulation of dry mass and the macronutrients (nitrogen, phosphorus, potassium, calcium and magnesium) in leaves, stems, Inflorescences, fruits and total. The soil covers did not affect accumulation of dry mass by tomato plants. The fruits behaved as preferential drain of the plant, reaching the end of the cycle with 48.6% of the total accumulated dry mass. The accumulation of nutrients followed the pattern of the accumulation of dry mass. Only N accumulation in the fruits, accumulation of K in leaves and total, and accumulation of Ca and Mg in fruits were influenced by soil covers. The highest averages for these characteristics were obtained when using the white polyethylene, TNT and uncovered soil. The nutrients more accumulated by plants were, in the order of magnitude: K> N> Ca> Mg> P, being N, P e K found in higher quantities in fruits, and Ca and Mg in leaves.
Growth, assimilate partition and accumulation of macronutrients by tomato SM-16 in different soil covers
Keywords: Lycopersicon esculentum Mill; Mulching; Acúmulo de massa seca; Marcha de absorção de nutrientes; Lycopersicon esculentum Mill; Mulching; Dry mass accumulation; March of absorption of nutrients; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA